The Influence of E-Wallets and Hedonism in Mediating the Relationship Between Lifestyle and Impulsive Consumption Behavior Among Gen Z Students - Kamelia Astuty; Tara Julita Eka Putri; Dilla Julia Azzarah; Evi Herlyaminda (Tractare: Jurnal Ekonomi-Manajemen, 2026)
The purpose of this study was to determine the potential revenue projections Land and Building Tax (PBB) in the city of Batam years 2014-2016..….…(CLICK C_ABSTRACT)